A NAC transcriptional factor BrNAC029 is involved in cytokinin-delayed leaf senescence in postharvest Chinese flowering cabbage. (15th March 2023) - Li, Fengjun; Shan, Youxia; Wang, Haobin; Jiang, Guoxiang; Ding, Xiaochun; Liang, Hanzhi; Wang, Chunlan; Kong, Xiangjin; Xie, Lihong; Jiang, Yueming
Highlights: CPPU maintained the cytokinin content and delayed leaf senescence. BrNAC029 was up-regulated during leaf senescence but suppressed by CPPU treatment. BrNAC029 served as a transcriptional activator and activated the transcriptions. A cytokinin analogue-BrNAC029-BrCKX1 regulatory chain regulated leaf senescence. Abstract: Both cytokinin and NAC transcription factors were reported to involve in leaf senescence. However, the mechanism of NAC transcription factors how to regulate cytokinin-delayed leaf senescence is still unknown. In this study, application of N -(2-chloro-4-pyridyl)- N '-phenylurea (CPPU), a cytokinin analogue, significantly delayed leaf senescence and maintained cytokinin content of Chinese flowering cabbage during storage. Meanwhile, the expression of an NAC transcriptional activator (BrNAC029) was increased but suppressed by CPPU treatment. Furthermore, BrNAC029 activated the expressions of chlorophyll catabolic genes BrPAO and BrSGR2, cytokinin oxidase gene BrCKX1 and senescence maker gene BrSAG113 by binding to their promoters. Additionally, overexpressions of BrNAC029 in tobacco and Arabidopsis accelerated leaf senescence and up-expressed the related genes. Taken together, it was suggested that BrNAC029 may serve as a transcriptional activator to activate the transcriptions of these related genes to eventually accelerate leaf senescence of Chinese flowering cabbage by promoting chlorophyll degradation and reducing endogenous cytokinin level.